Circular RNA circDUS2 Is a Potential Biomarker for Intracranial Aneurysm - Chen, Xin; Yang, Shuzhe; Yang, Junhua; Liu, Qingyuan; Li, Maogui; Wu, Jun; Wang, Hao; Wang, Shuo (Frontiers in Aging Neuroscience, 2021)
Background: CircRNAs have been found to play a crucial role in the pathological process of various kinds of diseases. However, the role of circRNAs in the formation and rupture of intracranial aneurysm is still unknown. Methods: Differentially expressed circRNAs profiles between superficial temporal arteries (n = 5) and intracranial aneurysms (n = 5) were analyzed using the Arraystar human circRNAs microarray. Quantitative real-time PCR was utilized to validate the differential expression of circDUS2. Fluorescence in situ hybridization (FISH) was meant for the location of circDUS2 in human brain vascular smooth muscle cell (HBVSMC). Structural analysis was used to speculate on the function of circDUS2. Results: Five hundred forty-three upregulated and 397 downregulated significantly in intracranial aneurysm as compared to superficial temporal arteries. Quantitative real-time PCR verified the elevated expression of the upregulated circDUS2. The FISH test revealed that circDUS2 is located in the cytoplasm of brain vascular smooth muscle cells. Conclusion: This study showed differential expression data of circRNAs between superficial temporal artery and intracranial aneurysm and revealed that circDUS2 is a potential molecular marker for intracranial aneurysm.